2016
DOI: 10.1155/2016/6052125
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Catheterization-Related Cerebral Infarction on Diffusion-Weighted Magnetic Resonance Imaging

Abstract: Introduction. The aim of this study was to examine the incidence and risk factors of catheterization-related CI in the contemporary era, using diffusion-weighted magnetic resonance imaging. Methods. We retrospectively analyzed consecutive 84 patients who underwent MRI (magnetic resonance imaging) after 2.81 ± 2.4 days (mean ± SD) of catheterization via aortic arch. We categorized the patients by the presence or absence of acute CI determined by diffusion-weighted MRI and analyzed the incidence and predictors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
(68 reference statements)
2
5
0
Order By: Relevance
“…In our study cohort, the ischaemic stroke and TIA rates in both age groups of ≤65 years old and >65 years old are low at all time points, in keeping with existing data from coronary intervention literature . Although higher rates of clinically silent cerebral microembolization have been reported in patients undergoing coronary interventions via TRA, it remains outside the scope of this paper, and its clinical significance remains unknown. Furthermore, stroke can also occur in TFA, as shown by a meta‐analysis of stroke after TRA vs. TFA arterial catheterization …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our study cohort, the ischaemic stroke and TIA rates in both age groups of ≤65 years old and >65 years old are low at all time points, in keeping with existing data from coronary intervention literature . Although higher rates of clinically silent cerebral microembolization have been reported in patients undergoing coronary interventions via TRA, it remains outside the scope of this paper, and its clinical significance remains unknown. Furthermore, stroke can also occur in TFA, as shown by a meta‐analysis of stroke after TRA vs. TFA arterial catheterization …”
Section: Discussionsupporting
confidence: 81%
“…With increasing age, the presence of atherosclerotic disease at the aortic arch poses a theoretical risk of plaque dislodgement and distal embolization to the intracranial circulation when transradial non‐coronary intervention is performed in elderly patients. Higher rates of cerebral microembolization have been detected using transcranial Doppler and MRI in patients undergoing coronary interventions via TRA . The presence of such plaques in the aortic arch is a known independent risk factor for strokes .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Morita et al reported that of the 84 patients who underwent MRI after catheterization, acute CI was found in 27 (32.1%) patients and the rate of CI after catheterization was significantly higher than other studies. However, because this study was a retrospective analysis and MRI was not performed for the series of catheterization procedures, the rate of CI may have been considerably overestimated 21 ) . In Korea, the incidence of asymptomatic CI after CAG performed before CABG and detected by MRI was 10.2% (20/197 patients), with IMA angiography as the independent risk factor 13 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In both of those patients, SBI were present (one and 11 lesions) with no clear correlation between the distribution and the symptomatology. Morita et al 24 identified dyslipidaemia, higher age, and number of catheters used as independent predictors for presence of SBI after catheterisation. Gutsche et al 5 classified the severity of atheromatous changes in the aorta based on CT images and demonstrated a significant association between stroke after TEVAR and high grade atheroma.…”
Section: Discussionmentioning
confidence: 99%